The PRECious trial PREdiction of Complications, a step-up approach, CRP first followed by CT-scan imaging to ensure quality control after major abdominal surgery: study protocol for a stepped-wedge trial. Issue 1 (December 2015) - Straatman, Jennifer; Cuesta, Miguel; Schreurs, W.; Dwars, Boudewijn; Cense, Huib; Rijna, Herman; Sonneveld, D.; den Boer, Frank; de Lange- de Klerk, Elly; van der Peet, Donald
Abstract Background After major abdominal surgery (MAS), 20 % of patients endure major complications, which require invasive treatment and are associated with increased morbidity and mortality. A quality control algorithm after major abdominal surgery aimed at early identification of patients at risk of developing major complications can decrease associated morbidity and mortality. Literature studies show promising results for C-reactive protein (CRP) as an early marker for postoperative complications, however clinical significance has yet to be determined. Methods A multicenter, stepped wedge, prospective clinical trial including all adult patients planned to undergo elective MAS. The first period consists of standard postoperative monitoring, which entails on demand additional examinations. This is followed by a period with implementation of postoperative control according to the PRECious protocol, which implicates standardized measurement of CRP levels. If CRP levels exceed 140 mg/L on postoperative day 3, 4 or 5, an enhanced CT-scan is performed. Primary outcome in this study is a combined primary outcome, entailing all morbidity and mortality due to postoperative complications. Complications are graded according to the Clavien-Dindo classification. Secondary outcomes are hospital length of stay, patients reported outcome measures (PROMs) and cost-effectiveness. Data will be collected during admission, three months and one year postoperatively. Approval by the medical ethics committee of the VU University Medical Center was obtained (ID 2015.114). Discussion the PRECious trial is a stepped-wedge, multicenter, open label, prospective clinical trial to determine the effect of a standardized postoperative quality control algorithm on postoperative morbidity and mortality, and cost-effectiveness. Trial registration www.ClinicalTrials.gov, NCT02102217 . Registered 5 February 2015.